Kepastian Hukum Penetapan Tarif Royalti Musik bagi Pelaku Usaha Kafe dan Transparansi Mengenai Penyaluran dan Distribusi Dana Royalti Musik - Andriano Andriano; Yenny Yuniawaty (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This journal discusses legal certainty regarding the determination of music royalty rates for café operators and transparency regarding the distribution of music royalties, but in practice, legal certainty regarding the clarity of royalty rates based on seating capacity and transparency in the distribution and disbursement of music royalties by the National Collective Management Organization (LMKN) and Collective Management Organizations (LMK) is still not guaranteed. The research method used is normative juridical with a legislative and conceptual approach, utilizing secondary data consisting of primary, secondary, and tertiary legal materials. In this study, the author used a descriptive analytical research method. The results of the study show that in the payment of music royalties by cafe businesses, there is uncertainty in determining the amount of royalty rates based on seating capacity and the distribution of royalty funds by the National Collective Management Institution (LMKN) and Collective Management Institutions (LMK). The National Collective Management Institution (LMKN) needs to clarify the determination of music royalty rates, and an alternative is to set music royalty rates per person based on the capacity of the cafe. In addition, the government, through the Ministry of Law, the National Collective Management Organization (LMKN), and the Collective Management Organization (LMK), needs to increase awareness and education regarding the distribution and disbursement of music royalties and the optimal use of technology in the music royalty information system.